Korelasi Motivasi, Fasilitas Belajar dan Prestasi Belajar Siswa - Suheri Widianto (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Developing learning motivation is affected the process of forming an autonomous learner. The effect of learning motivation by teacher has a very big impact because it helps the students to be an autonomous learner to reach their own achievement. Actually, developing learning motivation is very important and teachers should not ignore it. Because by motivating students, teachers will be easily reach the the goals of learning and education.